Carbon Dioxide Conversion Methods - Saqib, S. (Springer Nature, 2022)
The carbon capture and sequestration (CCS) community has searched with the economic viability of CO2 sequestration over the past few decades. In reality, however, it was not technically feasible until a recovered CO2 sector, like in the beverage or improved recovery of oil and gas, was created. The scientific community and business are slowly converging to the view that the demand offer is significantly constrained by the sequestration of CO2. Besides, the development of new consumer markets and income sources will prevail in the economic viability of this climate reduction strategy. The recovery of almost pure CO2 is a potential alternative. In the energy and chemical fields work is shown to shift both explicitly and indirectly towards CO2 consumption in the field of carbon capture and control. Within this segment, we have examined and measured advancement in research and development in this respect, the literature related to carbon capture, recycling, and consumption routes. Pathways for the usage of both physical and chemical CO2 are researched and main pathways are defined. The research is often reviewed to look at conditions for method development and success assessment. Â© 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.